Let the height of the kiwi be x, then the height of the ostrich is 20 + 4x.
20 + 4x = 108
4x = 108 - 20 = 88
x = 88/4 = 22
The height of the kiwi is 22 inches.
Answer:
i believe it is -21, but i'm not sure
Step-by-step explanation:
just foil the two to get a quadratic expression
n
y
=
−
x
−
4
To find the x-intercept, substitute in
0
for
y
and solve for
x
.
0
=
−
x
−
4
Solve the equa
−
x
−
4
=
0
.
−
x
−
4
=
0
Add
4
to both sides of the equation.
−
x
=
4
Multiply each term in
x
=
−
4
by
−
1
x
=
−
4
To find the y-intercept, substitute in
0
for
x
and solve for
y
.
y
=
−
(
0
)
−
4
Simplify
−
(
0
)
−
4
.
Multiply
−
1
by
0
.
y
=
0
−
4
Subtract
4
from
0
.
y
=
−
4
These are the
x
and
y
intercepts of the equation
y
=
−
x
−
4
.
x-intercept:
(
−
4
,
0
)
y-intercept:
(
0
,
−
4
)
not too sure
Answer with Step-by-step explanation:
We are given that
![f(x)=\frac{3x-1}{x}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B3x-1%7D%7Bx%7D)
For each real number ![x\neq 0](https://tex.z-dn.net/?f=x%5Cneq%200)
To prove that f is one -to-one.
Proof:Let
and
be any nonzero real numbers such that
![f(x_1)=f(x_2)](https://tex.z-dn.net/?f=f%28x_1%29%3Df%28x_2%29)
By using the definition of f to rewrite the left hand side of this equation
![f(x_1)=\frac{3x_1-1}{x_1}](https://tex.z-dn.net/?f=f%28x_1%29%3D%5Cfrac%7B3x_1-1%7D%7Bx_1%7D)
Then, by using the definition of f to rewrite the right hand side of this equation of ![f(x_1)=f(x_2)](https://tex.z-dn.net/?f=f%28x_1%29%3Df%28x_2%29)
![f(x_2)=\frac{3x_2-1}{x_2}](https://tex.z-dn.net/?f=f%28x_2%29%3D%5Cfrac%7B3x_2-1%7D%7Bx_2%7D)
Equating the expression then we get
![\frac{3x_1-1}{x_1}=\frac{3x_2-1}{x_2}](https://tex.z-dn.net/?f=%5Cfrac%7B3x_1-1%7D%7Bx_1%7D%3D%5Cfrac%7B3x_2-1%7D%7Bx_2%7D)
![3x_1x_2-x_2=3x_2x_1-x_1](https://tex.z-dn.net/?f=3x_1x_2-x_2%3D3x_2x_1-x_1)
![3x_1x_2-3x_1x_2+x_1=x_2](https://tex.z-dn.net/?f=3x_1x_2-3x_1x_2%2Bx_1%3Dx_2)
![x_1=x_2](https://tex.z-dn.net/?f=x_1%3Dx_2)
Therefore, f is one-to-one.